2011
DOI: 10.1002/art.30383
|View full text |Cite
|
Sign up to set email alerts
|

Novel assays of thrombogenic pathogenicity in the antiphospholipid syndrome based on the detection of molecular oxidative modification of the major autoantigen β2‐glycoprotein I

Abstract: ObjectiveBeta-2-glycoprotein I (β2GPI) constitutes the major autoantigen in the antiphospholipid syndrome (APS), a common acquired cause of arterial and venous thrombosis. We recently described the novel observation that β2GPI may exist in healthy individuals in a free thiol (biochemically reduced) form. The present study was undertaken to quantify the levels of total, reduced, and posttranslationally modified oxidized β2GPI in APS patients compared to various control groups.MethodsIn a retrospective multicent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 24 publications
1
92
0
1
Order By: Relevance
“…Evidence of the pathogenicity of anti-DI antibodies comes from both in-vitro and in-vivo studies. First, anti-DI antibodies were repeatedly observed to induce in-vitro prolongation of clotting time [3][4][5][6][7][8].…”
Section: Journal Of Hematology and Thromboembolic Diseasesmentioning
confidence: 99%
“…Evidence of the pathogenicity of anti-DI antibodies comes from both in-vitro and in-vivo studies. First, anti-DI antibodies were repeatedly observed to induce in-vitro prolongation of clotting time [3][4][5][6][7][8].…”
Section: Journal Of Hematology and Thromboembolic Diseasesmentioning
confidence: 99%
“…17 Many studies reported that antiplatelet agents, especially low to moderate doses of Aspirin, were used to prevent preeclampsia in high-risk patients. 18 Our patient was also started on a low dose of Aspirin (75mg/dl) as a preventive measure immediately after noting the fetal cardiac activity by USG but even then she developed PIH (probably due to the oral steroids) and thus started on anti-hypertensives.…”
Section: Grade V -Membranous Lupus Nephritismentioning
confidence: 99%
“…Additionally, monocytes from APS patients have an increased amount of intracellular reactive oxygen species [35]. In these conditions, disulphide bonds are formedand β2-GPI, becomes more immunogenic [36]. Evidence exists that patients with APS have a greater proportion of the oxidized versus the "free thiol form" than do patients with either other autoimmune diseases but without APS, patients with thrombosis without aPL or healthy volunteers (p<0,001 for all comparisons) [36].…”
Section: Considering Possible Mechanismsmentioning
confidence: 99%
“…In these conditions, disulphide bonds are formedand β2-GPI, becomes more immunogenic [36]. Evidence exists that patients with APS have a greater proportion of the oxidized versus the "free thiol form" than do patients with either other autoimmune diseases but without APS, patients with thrombosis without aPL or healthy volunteers (p<0,001 for all comparisons) [36]. In vitro studies showed that the "free thiol form" protects the endothelium from reactive oxygen species (ROS) [35] and that aPL promote formation of intracellular ROS.…”
Section: Considering Possible Mechanismsmentioning
confidence: 99%